If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+42=6(2x+7)
We move all terms to the left:
12x+42-(6(2x+7))=0
We calculate terms in parentheses: -(6(2x+7)), so:We get rid of parentheses
6(2x+7)
We multiply parentheses
12x+42
Back to the equation:
-(12x+42)
12x-12x-42+42=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 15x-2x-7=-14x-25 | | 180-x=490-6x | | 4x-34=82 | | 4(3m+3)=96 | | -4w-12=2(w-3) | | 9x-24+6x-5=x+9 | | 8-k=-10+8k | | 4w+15=−13;w4w+15=−13;w | | 113=-10a-7 | | 2(3+5x)=37 | | 8(4x+2)-6x-5=2(13x-4)+19 | | -2(10w+8)=-16w+20 | | (-54y-27)=-18 | | 7(y-2)+2y=-3(y+4)-2y | | -6(a-3)=11-7a | | 8n=5n-8 | | x^2+24-12=0 | | 3(2x+7)=40+25 | | 36-6y=12 | | 3(2x+4)=2(-6x-3) | | 12+8x=x-16 | | 3(r+1)=-25-4r | | 9x+4+3x+9=90 | | -9x+23=7x-41 | | r-6=6(8-3r) | | 2x+(80)+60=180 | | 5r=-41 | | 3x=-8.1 | | 4h+2(h-5)=3(2h-4) | | (5x−64)+3x=180 | | -13-2m=-5(5m-2) | | 37-3x=43 |